Design of Streaming Media Panoramic Video System Based on WebGL - Shi, Lu (fi=Turun yliopisto|en=University of Turku|, 2016)
2016 is the outbreak year of the virtual reality industry. In the field of virtual reality, 3D surveying plays an important role. Nowadays, 3D surveying technology has received increasing attention. This project aims to establish and optimize a WebGL three-dimensional broadcast platform combined with streaming media technology. It takes streaming media server and panoramic video broadcast in browser as the application background. Simultaneously, it discusses about the architecture from streaming media server to panoramic media player and analyzing relevant theory problem. This paper focuses on the debugging of streaming media platform, the structure of WebGL player environment, different types of ball model analysis, and the 3D mapping technology. The main work contains the following points: Initially, relay on Easy Darwin open source streaming media server, built a streaming service platform. It can realize the transmission from RTSP stream to streaming media server, and forwards HLS slice video to clients; Then, wrote a WebGL panoramic video player based on Three.js lib with JQuery browser playback controls. Set up a HTML5 panoramic video player; Next, analyzed the latitude and longitude sphere model which from Three.js library according to WebGL rendering method. Pointed out the drawbacks of this model and the breakthrough point of improvement; After that, on the basis of Schneider transform principle, established the Schneider sphere projection model, and converted the output OBJ file to JS file for media player reading. Finally implemented real time panoramic video high precision playing without plugin; At last, I summarized the whole project. Put forward the direction of future optimization and extensible market.